Concept of Child Development Theory Based on Perceptional and Motor Domains - Pradana, Rahadian Sakti; Sunardi, Sunardi; Susetyo, Budi (Proceeding of International Conference on Special Education in South East Asia Region, 2024)
Children's motor development is very important because children are confident in their environment, including when playing with their friends, children who grow and develop without motor skills will become inferior in carrying out tasks related to their skills. The aim of this research is to provide illustrated abilities in completing certain motor tasks, to provide the ability to be able to train children's body movements during motor development and to hone children's fine and gross motor skills. The method used by the author is a literature review analysis. In the process of motor perception, environmental stimuli that are relevant to movement are recognized, appropriate movement information is sent in the form of output to the muscles to produce various types of movement. Up to the fine and gross motoric stages, perceptual motor skills are also very important in improving children's motor skills and academic abilities.